The preventive effect on respiratory tract infections of Oscillococcinum®. A cost-effectiveness analysis - Colombo GL; Di Matteo S; Martinotti C; Oselin M; Bruno GM; Beghi GM (Dove Medical Press, 2018)
Giorgio L Colombo,1,2 Sergio Di Matteo,2 Chiara Martinotti,2 Martina Oselin,2 Giacomo M Bruno,2 Gianfranco M Beghi3 1Department of Drug Sciences, University of Pavia, Pavia, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche S.r.l., Health Economics & Outcomes Research, Milan, Italy; 3Unit of Pulmonary Rehabilitation, Hospital of Casorate Primo, Pavia, Italy Background: Anas barbariae hepatis et cordis extractum 200K (Oscillococcinum®) is used to treat and prevent seasonal colds and airway inflammatory affections, improve symptom control, and reduce the frequency of respiratory tract infection (RTI) episodes. The objective of this controlled observational study is to investigate, from the Italian National Health Service (NHS) point of view, the role of Anas barbariae hepatis et cordis extractum 200K in preventing RTIs and estimate the annual average cost per patient due to visits and medicines in a real-world setting, investigating whether this method of treatment can bring savings for the NHS.Methods: Data from a single center from 2002 to 2011 were used. The analysis examined 455 patients who suffered from respiratory diseases. Of the total number of patients, 246 were treated with Anas barbariae hepatis et cordis extractum 200K while 209 were not treated (Control group). All the data concerning RTI episodes, pharmacological treatments, and pneumological visits were extracted from the database.Results: It was found that, regardless of the diagnosis, the frequency of RTI episodes was always lower in patients treated with Anas barbariae hepatis et cordis extractum 200K; the difference between the numbers of events occurring was statistically significant in every class of patients (p<0.001). The costs that the NHS had to incur were significantly lower in the classes of patients treated (p<0.001).Discussion: The results indicate that Anas barbariae hepatis et cordis extractum 200K has a preventive effect on the onset of RTI episodes. The analysis shows that treating patients with Anas barbariae hepatis et cordis extractum 200K lowers costs for the NHS; this is primarily due to the fact that the medication causes fewer episodes of RTI to develop. This study suggests that the treatment with Anas barbariae hepatis et cordis extractum 200K could be helpful in preventing RTIs and improving the health status of patients who suffer from respiratory diseases, and it could lead to savings to the Italian NHS. Keywords: Oscillococcinum, prevention, respiratory tract infection, cost-effectiveness